FIRST THEROPOD RECORD FROM THE MARINE BATHONIAN OF JAISALMER BASIN, TETHYAN COAST OF GONDWANAN INDIA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2023)
Middle Jurassic theropods have a scanty record worldwide, especially from Gondwana. In India, where Jurassic theropods are particularly rare and only represented by a few isolated teeth and some badly preserved bones, there is currently no record of theropods from the Middle Jurassic of western India. Here we report the first theropod dental material from Middle Jurassic marine carbonate rocks of the Jaisalmer Basin, north-western India. The specimen consists of an incomplete shed tooth crown recovered from bioclastic intraformational conglomerate bed of the Bathonian Fort Member of the Jaisalmer Formation. A cladistic analysis performed on a dentition-based data matrix revealed that the isolated crown likely pertained to a non-coelurosaur averostran possibly from the mesial dentition of a ceratosaurid, a non-spinosaurid megalosauroid, or an allosauroid. This shed tooth provides evidence that at least one taxon of medium to large-bodied theropod lived on the Tethyan coast of NW India during the Middle Jurassic. This contribution marks the Jaisalmer Basin as a new promising area in India for dinosaurian remains from the Jurassic Gondwana.
Keywords: Middle Jurassic; theropod; non-coelurosaur averostran; Gondwana; Jaisalmer Basin; India.